High-resolution paleoclimatology of the Santa Barbara Basin during the Medieval Climate Anomaly and early Little Ice Age based on diatom and silicoflagellate assemblages in Kasten core SPR0901-02KC. (11th November 2015) - Barron, John A.; Bukry, David; Hendy, Ingrid L.
Abstract: Diatom and silicoflagellate assemblages documented in a high-resolution time series spanning 800 to 1600 (AD) in varved sediment recovered in Kasten core SPR0901-02KC (34°16.845′ N, 120°02.332′ W, water depth 588 m) from the Santa Barbara Basin (SBB) reveal that SBB surface water conditions during the Medieval Climate Anomaly (MCA) and the early part of the Little Ice Age (LIA) were not extreme by modern standards, mostly falling within one standard deviation of mean conditions during the pre anthropogenic interval of 1748–1900. No clear differences between the character of MCA and the early LIA conditions are apparent. During intervals of extreme droughts identified by terrigenous proxy scanning XRF analyses, diatom and silicoflagellate proxies for coastal upwelling typically exceed one standard deviation above mean values for 1748–1900, supporting the hypothesis that droughts in southern California are associated with cooler (or La Niña-like) sea surface temperatures (SSTs). Increased percentages of diatoms transported downslope generally coincide with intervals of increased siliciclastic flux to the SBB identified by scanning XRF analyses. Diatom assemblages suggest only two intervals of the MCA (at ∼897 to 922 and ∼1151–1167) when proxy SSTs exceeded one standard deviation above mean values for 1748 to 1900. Conversely, silicoflagellates imply extreme warm water events only at ∼830 to 860 (early MCA) and ∼1360 to 1370 (early LIA) that are not supported by the diatom data. Silicoflagellates appear to be more suitable for characterizing average climate during the 5 to 11 year-long sample intervals studied in the SPR0901-02KC core than diatoms, probably because diatom relative abundances may be dominated by seasonal blooms of a particular year.